CHARACTERIZATION OF ROBUSTA COFFEE (Coffea canephora) FROM TULUNGREJO FERMENTED WITH Saccharomyces cerevisiae - Dionesius Budi; Wahyu Mushollaeni; Yusianto Yusianto; Atina Rahmawati (Jurnal Agroindustri, 2020)
Robusta coffee (Coffea canephora) is one type of coffee that is cultivated by the people of Tulungrejo Village, Malang Regency. Until now, the coffee is still sold fresh or dry, because this coffee has a bitter taste and is quite acid so that if it is made into a grounded coffee and consuming it with a high enough frequency it will cause an increase in stomach acid. The presence of caffeine, as well as several types of secondary metabolites, caused the bitter and sour taste in Robusta coffee. Therefore, need a process that is easy, inexpensive, and can be directly applied by the community to reduce levels of caffeine and acid. Fermentation using Saccharomyces cerevisiae yeast is one of the stages of the processing of agricultural products that are most often carried out by the community. However, the effect of fermentation of Robusta coffee from Tulungrejo using S. cerevisiae has never been studied to reduce its acid content. Therefore, this study aimed to obtain the best yeast concentration and fermentation time in making Robusta ground coffee from Tulungrejo so that the acid content was in line with ground coffee standards. The best treatment was obtained by adding 2% yeast with 10 hours of fermentation time. This treatment produces ground coffee which has a pH of 5.275; water content 1.75%; ash content 4.81%; and caffeine content of 5.6055 mg/ml. The levels of caffeine and pH had met SNI 1-3542-2004 standards